2014
DOI: 10.1037/h0099842
|View full text |Cite
|
Sign up to set email alerts
|

The role and meaning of interim housing in housing first programs for people experiencing homelessness and mental illness.

Abstract: The housing first (HF) model for individuals experiencing homelessness and mental illness differs by design from traditional models that require consumers to achieve "housing readiness" by meeting program or treatment prerequisites in transitional housing settings prior to permanent housing placement. Given a growing body of evidence for its favorable outcomes and cost effectiveness, HF is increasingly seen as an alternative to and argument against these traditional programs. As such, it is important that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Some of the sites experimented with single-site or interim housing alternatives for these participants after they had been evicted several times from independent housing (Zerger et al 2014). Also, previous qualitative research has found that staff who persevere in connecting with consumers, are kind, and provide one-to-one support that promotes service engagement (Padgett et al 2008a;Stanhope 2012;Stanhope et al 2009).…”
Section: Participant Factorsmentioning
confidence: 99%
“…Some of the sites experimented with single-site or interim housing alternatives for these participants after they had been evicted several times from independent housing (Zerger et al 2014). Also, previous qualitative research has found that staff who persevere in connecting with consumers, are kind, and provide one-to-one support that promotes service engagement (Padgett et al 2008a;Stanhope 2012;Stanhope et al 2009).…”
Section: Participant Factorsmentioning
confidence: 99%
“…Eleven qualitative studies were found related to homelessness and establishing a home. The eleven qualitative studies employed two phenomenology (Burlingham et al, 2010;Raphael-Greenfield & Gutman, 2015), two grounded theory (Chen & Ogden, 2012;Fisher et al, 2014), three descriptive (Henwood et al, 2013;Mayberry et al, 2014;Polvere et al, 2013), two exploratory (Patterson et al, 2015;Zerger et al, 2014), one case study (Ogden, 2014), and one Community Based Participatory Research (CBPR): Photovoice (Peterson et al, 2012).…”
Section: Methodological Reviewmentioning
confidence: 99%
“…Among the qualitative studies, the majority of the studies were conducted in the U. S., while 27% were conducted in Canada (Patterson et al, 2015;Polvere et al, 2013;Zerger et al, 2014) and one in England (Raphael-Greenfield & Gutman, 2015). Various disciplines were represented in the studies including psychology/psychiatry, social work, Department of Human and Organizational Development, health sciences, communications, occupational therapy, and medicine/public health.…”
Section: Methodological Reviewmentioning
confidence: 99%
See 2 more Smart Citations